Jivan Ready For A Cop's Life - Hockey Ace Closer To Dream after Earning UPM Degree - Sunday Star, Aftar Singh (2008)
National hockey player M. Jivan's childhood dream was to become a police officer. And this could become a reality for the Penang-born player, who obtained a degree in the Human Resource Development during the convocation of Universiti Putra Malaysia (UPM) in Serdang yesterday.